RELATIONSHIP OF FAMILY WITH THE INPATIENT OF CONGESTIVE HEART FAILURE OF PATIENT IN THE CARDIOVASCULAR AND BRAIN CENTER OF RSUP PROF DR.R.D KANDOU MANADO - Dewi Mayasari Riu, Silvia; Rahmat Hidayat Djalil (Sean Institute, 2022)
Patient sometimes back to the clinic or hospital because of relapse of heart failure. Mostly relapse of heart failure occur because the patient does not meet the recommended therapy, such as the patient unable to carry out appropriate treatment therapy, ignore the restriction of diet, do not comply with medical follow-up, perform excessive physical activity, and cannot recognize symptoms of relapse. The aim of this research is to determine the relationship of family with the inpatient of congestive heart failure of patient in the cardiovasculer and brain center (CVBC) ward of RSUP Prof Dr.R.D Kandou Manado. Cross sectional descriptive analytic used in this research, respondents was 33 people using total sampling. Collecting data used questionnaires and observation sheets. Then Analyzed with chi square statistical test. The outcome of the research was most of age 46-55 years old 9 respondents (27.3%), most of gender was male 20 respondents (60.6%) most of education was SMA 29 respondents (87.9%), most of occupation was household workers 13 respondents (39 ,4%). The outcome of chi square test obtained p value <α 0.05. The conclusion of this research is there is a relationship between the support of family and the incidence of re-inpatient. hoped that the hospital able to use this research as a basis for evaluating the implementation of good discourse planning.